Strategi Pembelajaran Al-Qur’an dengan Metode Ummi Di MI Muhammadiyah 1 Jombang - Muslimin, Juni; Romelah, Romelah; Mardiana, Dina (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Determining the appropriate strategy for Quranic learning in an era where numerous new Quranic learning methods are emerging is crucial. The selection of the right learning strategy is influenced by the teachers' circumstances, students' abilities, and the condition of facilities at the school. Additionally, a comfortable and conducive classroom or school environment is another important factor supporting the success of the learning process. This research aims to discuss the implementation of Quranic learning strategies using the Ummi method and its execution. The research method employed is qualitative with a case study approach. The results of this study are: 1) The Quranic learning strategies used are classical reading and listening, and pure classical reading and listening. 2) The implementation of Quranic learning follows the seven steps of the Ummi method for Quranic learning. The Ummi method refers to the established learning stages by the Ummi Foundation, supplemented by flagship programs in the execution process.